The changes of large intestine cavity’s microbiota in patients with HIV infection - Savinova, O; Gorobchenko, K; Nikolaeva, L; Bolshakova, G; Majstat, T; Djachenko, A (Annals of Mechnikov's Institute, 2020)
Introduction. Infections of the gastrointestinal tract are caused by a wide range of fungi, viruses and bacteria. The great value has the ratio of microorganisms. There are certain regularities inmicroecological system of intestinal microflora. Thus, bifidous bacteria should be more than lactobacterium; enterobacteria – more than enterococcus; E.faecalis more than E.faecium. However, these differences should be at least one or two orders of magnitude. An important indicator is the ratio of enterobacteria and enterococcus. Material & methods. In the paper were used following materials and methods: bacteriological and statistical. The conditions of intestinal microbiocenosis were evaluated according to the methodical instructions about researches of fecal masses on dysbiosis and modern methods of correction of intestinal dysbiosis that included identifying of anaerobic and facultative anaerobic microorganisms, staphylococci, enterococci, opportunistic enterobacteria, Proteus spp., Klebsiella spp., P.aeruginosa, C.albicans.Bacterial cultures were identified by standard techniques.Statistical analysis of the results was performed by the standard method of determining the average value and its standard deviation (M + m) and Student's t-test.The reliability of the difference was evaluated at the level of probability p <0.05. The experiments’ data were processed using software applications Microsoft Excel 2003 and «Biostat-6". Results & discussion. We studied the species and quantitative composition of intestinal microflora of patients with HIV infection. All studied patients had disrupted quantitative and qualitative composition of intestinal flora. The changes were identified both anaerobic and aerobic microorganisms. Abnormality in the components of microbiota was manifested by reduction in the number of microbiota in the absence of conditionally pathogenic microflora. In the first place by deficit of microorganisms were bifidus bacteria. According to our research in 94.1+4.01% of cases bifidus bacteria were found in the amount of <106 CFU/grams and in 5.9+4.04 % of cases they were founded in the amount of 107 CFU/grams. The second place by importance is occupied by lactobacillus. In comparison with the norm patients with HIV infection had this indicator reduced and amounts to 88,2+5,53% in ≤105 CFU/grams and 11.8+5.53% in 106–107 CFU/grams. Bacteroides from the group of anaerobic bacteria was not found in any patient. Among the group of aerobic bacteria leading representative was E.сoli, which belongs to the group of obligate microflora. 19 patients had E.сoli in the amount of ≤106 CFU/grams, which made up to 56% while the norm is 108 CFU/grams of faeces. 56% of patients with the 3rd clinical stage of HIV had simultaneous shortage of bifidus bacteria, lactobacillus and Escherichia. Hemolytic E.coli were detected in small amounts of 2.9 + 2.93%. The results of microbiological studies of fecal on dysbacteriosis shown that despite the decrease of bifidus bacteria over 40 times in patients with the 2–3rd clinical stage of HIV infection conditionally pathogenic microflora appeared in small amounts, such as hemolytic isolates of E. coli 2.9 + 2.93%, S.aureus in amount of >104 CFU/grams in 11,8 + 5,53%, S.epidermidis in amount of > 105 CFU/grams in 32,4 + 8,03%, C.albicans in amount of > 104 CFU/grams in 11,1 + 6,59% and 1 patient had Clostridium in amount > 103 CFU/grams, which was 3 + 2,93%. These data show that patients with HIV infection is detected at the same time reducing number of anaerobic microflora (bifidus bacteria and lactobacilli) and aerobic microflora, a leading representative of which is intestinal E.coli irrespective of the clinical stage of the disease. Association of these microorganisms is 56%. To this attach indicators of reduction E.faecalis and E.faecium. Taking into account the features of obligate microfloras’ functions (bifidus bacteria, lactobacillus, E.coli), its lack has a negative impact on microecological system of the human body and reduces immunomodulatory effect on humoral and cellular immunity. So one of the issues which will have a positive impact on the health of patients with HIV infection is a normalization of obligate microflora deficit and reducing of opportunistic microflora. The conducted researches point to the need of microbiological analysis of fecal on dysbiosis for the patients with HIV infection and depending on the revealed dysbiotic changes making correction of microflora by biological agents. To correct the number of anaerobic bacteria (bifidus bacteria, lactobacillus) use of bacterial preparations is not enough for only one month. It is necessary to continue taking of medicinefor at least one month under the control of microbiological studies. The positive dynamics of the microflora of the large intestine points to changes that may be found in the immune system of the person that takes biological preparations. The close interaction between the microbiota of intestinal canal and the immune system leads to the formation of non–specific resistance of the organism. In this regard, the big importance has a modulating effect of intestinal microflora on products of cytokines, which are characterized by a wide range of biological effects. Conclusion. 1. Patients with HIV infection irrespective of the clinical stage of the disease have deficit both anaerobic (bifidobacteria and lactobacilli) and facultative anaerobic microorganisms. 2. E.coliis the leadingmicroorganismamong the facultativeanaerobicintestinal microflora, its amount of has been reducedto levels<106CFU /mL at56% at the patients. 3. Correction of patients' microflora by bacterial agents showed that the number of E.coli already in a month have reached the normal level in 100% of cases.